ANALYZING SENTENCES INTO COMPONENTS AND SYNTAXEMAS IN THE INTERPRETATION OFSYNTACTIC UNITS - Abdukodirova Yulduz Safaraliyevna (Western European Studies, 2024)
As every subject has its own methods and styles theoretically and practically, every theme as a little branch gets own appropriate ways while explaining that theme. Grammar is treated is one of the scientific fields by which learner makes the model of the language. Nearly, students’ acquiring depends on teachers’ ability. In other words, teachers should be able to use all proper methods of making grammar themes comprehensible. This article is devoted to the problems that arise in the process of learning English grammar, in the process of analyzing the sentence into components and syntaxes. The authors have proposed the solutions to the obstacles on analyzing them thoroughly.
Keywords: Component and syntax analysis; distributive; division into direct participants